Integrating somatic variant data and biomarkers for germline variant classification in cancer predisposition genes. Issue 11 (11th October 2018) - Walsh, Michael F.; Ritter, Deborah I.; Kesserwan, Chimene; Sonkin, Dmitriy; Chakravarty, Debyani; Chao, Elizabeth; Ghosh, Rajarshi; Kemel, Yelena; Wu, Gang; Lee, Kristy; Kulkarni, Shashikant; Hedges, Dale; et al.
Abstract: In its landmark paper about Standards and Guidelines for the Interpretation of Sequence Variants, the American College of Medical Genetics and Genomics (ACMG), and Association for Molecular Pathology (AMP) did not address how to use tumor data when assessing the pathogenicity of germline variants. The Clinical Genome Resource (ClinGen) established a multidisciplinary working group, the Germline/Somatic Variant Subcommittee (GSVS) with this focus. The GSVS implemented a survey to determine current practices of integrating somatic data when classifying germline variants in cancer predisposition genes. The GSVS then reviewed and analyzed available resources of relevant somatic data, and performed integrative germline variant curation exercises. The committee determined that somatic hotspots could be systematically integrated into moderate evidence of pathogenicity (PM1). Tumor RNA sequencing data showing altered splicing may be considered as strong evidence in support of germline pathogenicity (PVS1) and tumor phenotypic features such as mutational signatures be considered supporting evidence of pathogenicity (PP4). However, at present, somatic data such as focal loss of heterozygosity and mutations occurring on the alternative allele are not recommended to be systematically integrated, instead, incorporation of this type of data should take place under the advisement of multidisciplinary cancer center tumor‐normal sequencing boards.